2024
DOI: 10.1109/jphot.2024.3379234
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Single-Mode Power in VCSELs With Antiresonant Oxide Island

Marta Więckowska,
Maciej Dems

Abstract: This article focuses on the optimization of single-mode power in Vertical Cavity Surface Emitting Lasers (VCSELs) through the strategic integration of an antiresonant oxide islands. Using a gallium arsenide-based VCSEL as a case study, we explore the influence of oxide island parameters on lateral mode discrimination in term of threshold currents and emitted powers. The analysis confirms non-uniform variations in threshold currents, with varying oxide island position and size. Leveraging the spatial hole burni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Once they reach the active region, defects would rapidly climb and expand, due to the built-in strain inside the quantum wells, which eventually leads to device failure once the defect density reaches a critical level. Although there are advanced technologies to mitigate the possible defects around the mesa sidewall, particularly near the oxidized ring [12], [14], the traditional processing technology [15], [16] seems still common for fabrication simplicity and/or cost-effectiveness. Moreover, although in advanced VCSELs, the remaining reliability issue is the wear-off degradation which shows a slow and gradual deterioration of the device performance, we still found that the random failure rate in some production batches of devices was not to our satisfactory, even when the mesa and oxidation were processed with the state-of-2 PJ-014683-2024 the-art technology.…”
Section: Introductionmentioning
confidence: 99%
“…Once they reach the active region, defects would rapidly climb and expand, due to the built-in strain inside the quantum wells, which eventually leads to device failure once the defect density reaches a critical level. Although there are advanced technologies to mitigate the possible defects around the mesa sidewall, particularly near the oxidized ring [12], [14], the traditional processing technology [15], [16] seems still common for fabrication simplicity and/or cost-effectiveness. Moreover, although in advanced VCSELs, the remaining reliability issue is the wear-off degradation which shows a slow and gradual deterioration of the device performance, we still found that the random failure rate in some production batches of devices was not to our satisfactory, even when the mesa and oxidation were processed with the state-of-2 PJ-014683-2024 the-art technology.…”
Section: Introductionmentioning
confidence: 99%